Global Trigger Tool methodology to detect adverse events: pilot study at Academic Hospital of Udine. (30th September 2020) - Scarpis, E; Degan, S; De Corti, D; Mellace, F; Cocconi, R; Farneti, F
Abstract: Introduction: Identification and measurement of adverse events (AEs) is crucial for patient safety in order to monitor them over time and to implement quality improvement programs, testing if they are effective. Global Trigger Tool (GTT) has been proposed as a low-cost method, being also the most effective to detect AEs. This study aims to describe the number of triggers, the rate and level of AEs identified by GTT and the most frequent type of AE. Methods: The Italian version of the GTT was used. Ten paper-based clinical records (CRs) randomly selected every 2 weeks were reviewed from January to April 2019 by three independent reviewers (two nurses, one doctor) at the Academic Hospital of Udine. The AEs rates calculated are: AEs per 1, 000 patient-days, AEs per 100 admissions, percentage of admissions with an AE. AEs were classified by harm levels according to National Coordinating Council for Medication Error Reporting and Prevention (NCC MERP). Results: CRs reviewed were 80. Mean age of the patients was 69.3±16.4, women were 37.5%. Mean hospitalisation was 16.8±15.3. Nine were the cases of re-hospitalisation within 30 days (11.3%). The total number of trigger was 156. AEs were 31, with at least one AE on 27.5% of admissions, 38.8 AEs per 100 admissions and 23 AEs per 1, 000 patient-days. AEs with harm level E, F and H were respectively 5 (16.1%), 24 (77.4%) and 2 (6.5%). The most frequent type of AE were hospital acquired infections with 15 cases (48.4%). Conclusions: The most frequent type of AE was the hospital acquired infections. Rates and levels of AEs were higher than other international studies, probably because of the limited number of CRs reviewed. Key messages: Global Trigger Tool is an effective method to detect adverse patient safety events in order to monitor them over time. The most frequent type of adverse events was the hospital acquired infections.